Peran Ojek Online Wanita Guna Menambah Perekonomian Keluarga - Siska Novy Isaroh; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2023)
The existence of online motorcycle taxis currently rovides many benefits such as increasing the unemployment rate in Indonesia and increasing people's economic income, especially for online motorcycle taxi drivers where online motorcycle taxis that have joined can help the family economy. This type of research uses field research that conducts interviews with informants to obtain primary data. The role of women workers who work as online motorbike taxis is a dual role that is owned by housewives besides cooking, caring for their daughters, they can also work as online motorbike taxis, their efforts aim to help improve the family's economy which is something very extraordinary. This research aims to increase knowledge about the position and role of women, which can also help ease the financial burden on the family. This study uses a qualitative method with a descriptive approach and data obtained through in-depth interviews. The object of research is a woman online motorcycle taxi driver in Candi-Sidoarjo. The information they got was that they changed professions during the Covid-19 pandemic, where previously factory workers now chose to become online motorcycle taxi drivers.